Diversity in Sinitic languages - Chappell, Hilary 1955- (Oxford Oxford University Press, 2015)
This book presents new research into the great structural diversity found in Sinitic languages. While many studies focus principally on Standard Mandarin, this work draws on extensive empirical data from lesser-known languages, and seeks to dispel many recurrent linguistic myths about the Sinitic language family. Part I presents findings that show the important interplay of research into diachronic linguistics and typology in China, beginning with a discussion of how to tackle the issue of linguistic diversity in Sinitic languages. Chapters in Part II examine the Sinitic languages from a crosslinguistic perspective with pan-Sinitic explorations of demonstrative paradigms; bare classifier phrases in relation to the coding of definiteness; and of the diachronic development of two main structures for comparatives of inequality with respect to issues in language contact. Part III is devoted to individual studies of linguistic micro-areas in China: Pinghua and the Guangxi Autonomous Region in the far South of China; Shaowu Min in the northwestern corner of Fujian province; the Wu dialect of Fuyang; and the Hui'an Southern Min dialect in the South of Fujian province.
Includes bibliographical references (pages 273-302) and indexes.
Keywords: Chinese language -- Dialects; Chinese language -- Dialects -- Grammar